Tablet characteristics and pharmacokinetics of orally disintegrating tablets containing coenzyme Q10 granules prepared by different methods - Kashiwagura Yasuharu; Takusagawa Shota; Ikematsu Yasuyuki; Tanaka Shimako; Namiki Noriyuki; Uchida Shinya (Acta Pharmaceutica)
This study aimed to elucidate the characteristics and pharmacokinetics of orally disintegrating tablets (ODTs) containing coenzyme Q10 (CoQ10) granules prepared by spray drying, hot-melting, and wet granulation. The hardness and disintegration times of CoQ10-ODTs containing 5 % crospovidone were 61.6–81.8 N and < 30 s, respectively; these values indicate that the as-prepared ODTs were adequate for clinical use. The hardness and disintegration times of all ODTs did not change significantly after a 28-day storage period at 30 °C/10 % relative humidity (RH), but storage under high temperature and humidity affected their characteristics. The dissolution and pharmacokinetics of CoQ10-ODTs showed that ODTs prepared using the spray-drying method had the highest dissolution and absorbability among the CoQ10-ODTs tested. These results provide useful information for the preparation of ODTs using CoQ10.